PEMECAHAN MASALAH PROGRAM LINIER BERKOEFISIEN INPUT PARAMETRIK MENGGUNAKAN PARAMETRIC LINEAR PROGRAMMING - Marpaung, Budi (Teknik dan Ilmu Komputer, 2012)
Parametric Linear Programming is a development model of sensitivity analysis in which the inputs coefficient changes simultaneously. This model develops problem-solving in which the input coefficients are not definitely known, but it can be estimated within a certain interval according to the expected level of confidence. This paper outlines the benefits of Parametric Linear Programming to analyze the fluctuations impact of the objective function coefficients and constants of the optimal solution. It was proven that the input coefficient change at certain intervals did not alter the optimal solution that has been obtained previously.ÃÂ Keywords:ÃÂ parametric programming, level of confidence, constraint, resources, pertubation vector, righ-hand-side, optimal, Simplex Method